(untitled) (Libellarium: journal for research in the field of information and related sciences, 2009)
This research is based on two main claims. First, (Kraaykamp, 1993) the differences in reading habits are a result of differences in cultural behavior, and second, (Bourdieu, 1984) cultural participation is conditioned by social class membership determined by the basic demographic profile of examinees (education, income, profession). This influenced our test sample choice - we focused on three main locations to collect our data: bookstores and libraries, Faculty of Philosophy in Zagreb, and Faculty of Economics in Osijek. The research methodology used in this paper relies on earlier theoretical findings on ‘the factors that determine the predilection for reading’ (Stockmans, 1999), as well as on the planning, implementation, data collection, and data analysis using the methods of multivariate statistics. In order to achieve statistical quantification, we created a questionnaire for measuring the attitudes of readers (n=400). The data was collected in 2007 using the ‘face to face’ method in the selected central locations (bookstores and libraries, Faculty of Philosophy in Zagreb, and Faculty of Economics in Osijek). This paper presents the characteristics of the study and the results of the statistical analysis of data showing examinee’s grading of their interest in selected literary genres. Research results are discussed with the focus on their importance for publishing, which deals with production, promotion and selling of books, and as such directly depends on readers’ attitudes.